Literature Review : Pengaruh Audit Manajemen, Sistem Pengendalian Internal, Peran Audit Internal, Terhadap Good Corporate Governance Badan Usaha Milik Negara - Adelia Putri; Tuti Meutia (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study discusses the influence of management audit, internal control system, and the role of internal audit on the implementation of good corporate governance principles in SOEs in Indonesia. The findings show that management audit practices, internal control systems, and internal audits have a significant role in supporting good corporate governance. The relationships found in this study highlight the importance for companies to develop and strengthen internal control systems, improve the effectiveness of internal audits, and ensure management's commitment in implementing good Good Corporate Governance (GCG) practices within the company. Based on the literature, it can be seen that management audit, internal control system, and the role of internal audit have a significant influence on Good Corporate Governance practices. Several studies have also shown that the implementation of GCG principles helps companies improve transparency, accountability, and compliance with organizational regulations